INTRODUCTION OF ACTINOMYCETES STARTER ON COFFEE FRUITS FERMENTATION TO ENHANCE QUALITY OF COFFEE PULP - Kurniawati, Nurleni; Meryandini, Anja; Sunarti, Titi Candra (Emirates Journal of Food and Agriculture, 2017)
Coffee pulp contains bioactive compounds such as polyphenols and aldehydes, which are covalently linked to the pulp cell wall. The research aimed to determine of potential Actinomycetes concortia on the degradation of coffee pulp to enhance the yield and quality of coffee pulp polyphenol extracts. In this study, whole coffee fruit were fermented in solid-state cultivation by using concortia of Streptomyces exfoliatus 42 and Streptomyces costaricanus 45I-3 that having cellulolytic and xylanolytic activities. The introduction of Actinomycetes starter accelerated the fermentation which caused the degradation of lignocellulosic components of coffee pulp, and significantly effects on the yield of bioactive compounds such as polyphenols, anthocyanins, tannins, and catechin. Compared to the spontaneous fermentation of coffee fruit, the highest yield of bioactive components extracts produced from 6th day incubation for total polyphenols (1.20 mg mL-1), anthocyanin (109.95 mg mL-1) and the highest yield of catechin (10.38 mg mL-1) produced form 3th day incubation, but introduction of Actinomycetes reduced the tannin contents after fermentation.